Pengembangan Media Pembelajaran Interaktif Gosivo Terhadap Kemampuan Mengenal Huruf Vokal Pada Anak Usia 4-5 Tahun - Prisa Dian Sugiarti; Kartika Rinakit Adhe; Muhammad Reza; Dewi Komalasari (Journal of Innovative and Creativity, 2026)
This study is motivated by the low ability of children aged 4–5 years at TK Puri Cendekia to recognize vowel letters, due to the limited variety of learning media used. Therefore, this research aimed to develop and examine the feasibility of Gosivo (Google Sites Vowel) media in improving vowel recognition skills of children aged 4–5 years at TK Puri Cendekia. The sample used in this study consisted of 14 children. This research employed a development research method, namely Research and Development (R&D), using the 4D development model. The results showed that the feasibility of the Gosivo media, based on validation by media experts, obtained a percentage score of 95%, while validation by material experts obtained a percentage score of 90.6%, both categorized as very feasible. The practicality test results showed a percentage score of 100%, which falls into the very practical category. Meanwhile, the effectiveness of the Gosivo interactive learning media was indicated by an improvement in children’s ability to recognize vowel letters, as shown by the Wilcoxon test results with Asymp. Sig. (2-tailed) of 0.001 < 0.05 and an N-Gain value of 82%, which is categorized as high.The research findings indicate that children became enthusiastic when learning vowel letters through well-organized materials, beginning with the introduction of sounds, shapes, and images representing each letter. The implications of the development of Gosivo media show that the use of interactive learning media designed according to the developmental stages of children aged 4–5 years can increase children’s engagement, interest, and ability in recognizing vowel letters.